Analisis Peran Kepala Sekolah dalam Meningkatkan Kinerja Guru di SDI CIII Wolomarang - Sonya Kristiani Maria; Paulina Nelce Mole (Journal on Education, 2023)
This study aims to describe the role of the principal in improving teacher performance at SDI CIII Wolomarang. The research used is descriptive qualitative. Data collection techniques are carried out through interviews, observations and documentation. The test of the validity of the data used in this study is a study using source triangulation. Miles and Huberman's data analysis techniques start from the stages of data collection, data reduction, data presentation and drawing conclusions. The results of this study show that: the role used by the principal is the role of Educator, Manager, Administrator, Innovator, Motivator, Supervisor, and Leader. This role has an effect in improving teacher performance, although it is not optimal and still needs to be evaluated and the principal continues to improve teacher performance for the advancement of the quality of school education.